2006
DOI: 10.1002/ijc.22140
|View full text |Cite
|
Sign up to set email alerts
|

Circulating enterolactone and risk of endometrial cancer

Abstract: It has been suggested that phytoestrogens protect against hormone-dependent cancers. Lignans are the main class of phytoestrogens in Western diets. We conducted a prospective study of endometrial cancer and circulating levels of the main human lignan, enterolactone. The design was a case-control study nested within 3 prospective cohort studies, in New York, Sweden and Italy. Serum or plasma samples had been collected at enrollment and stored at 280°C. A total of 153 cases, diagnosed a median of 5.3 years after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 33 publications
2
6
1
1
Order By: Relevance
“…The median enterolactone level measured in our study is in accordance with the range of previously published circulating enterolactone concentrations in the US and Europe [49,29,50,36,37,30,51,52,28,53,54,33,55], but lower than that in Asia [56]. We did not observe an association between plasma enterolactone, a biomarker of lignan intake, and breast cancer risk either overall or by hormone receptor status.…”
Section: Discussionsupporting
confidence: 91%
“…The median enterolactone level measured in our study is in accordance with the range of previously published circulating enterolactone concentrations in the US and Europe [49,29,50,36,37,30,51,52,28,53,54,33,55], but lower than that in Asia [56]. We did not observe an association between plasma enterolactone, a biomarker of lignan intake, and breast cancer risk either overall or by hormone receptor status.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, only three case-control studies [911] have reported on the role of phytoestrogens on endometrial cancer risk, with conflicting results. A few additional studies examining the impact of soy foods, the main source of isoflavones, tended to suggest an inverse association [10, 12].…”
Section: Introductionmentioning
confidence: 99%
“…The main dietary precursors are identified as SECO, matairesinol and recently lariciresinol and pinoresinol (Milder et al, 2005b). As this transformation again was shown to be performed uniquely by bacteria (Bowey et al, 2003) and as the enterolignans would have increased biological activity (McCann et al, 2005;Kuijsten et al, 2006;Saarinen et al, 2006;Zeleniuch-Jacquotte et al, 2006), it can be concluded that intestinal bacteria also determine health effects related to lignan intake.…”
Section: Bioavailability Of Phyto-oestrogens: the Role Of Intestinal mentioning
confidence: 99%
“…, 2006; Saarinen et al. , 2006; Zeleniuch‐Jacquotte et al. , 2006), it can be concluded that intestinal bacteria also determine health effects related to lignan intake.…”
Section: Bioavailability Of Phyto‐oestrogens: the Role Of Intestinal mentioning
confidence: 99%